IMPLEMENTASI PROGRAM ASISTENSI MENGAJAR DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA - Risnadia, Risnadia; Ichwan, Aghnia Auliannisa; Priatna, Muhammad Fathin; Zahra, Aulia Tu; Navisa, Elena Trida; Rosdianti, Dina; Rafianti, Isna; Ihsanudin, Ihsanudin (LPPM Universitas Bina Bangsa, 2025)
The research conducted aims to implement various Teaching Assistance programs in order to increase students' motivation to learn mathematics. This study also aims to determine whether the role of the Teaching Assistance Program is an increase in student learning motivation. This research was conducted in one of the public high schools located in Serang Regency. The research method used is a descriptive qualitative approach. The target of this research is class X students. The data collection techniques used were questionnaires, interviews, participatory observation and documentation. The results of this study are teaching assistance programs such as technology-based learning using the Tiktok application, technology-based learning using Kahoot, student center learning-based learning using LKPD and Ice Breaking Dream can increase students' motivation to learn mathematics. This research shows that the teaching assistance program plays an important role in maintaining, growing, and increasing student learning motivation, especially in grade X high school students.